2011
DOI: 10.1002/col.20658
|View full text |Cite
|
Sign up to set email alerts
|

A new model for chromotherapy application

Abstract: Although the effects of colors on the emotion have been studied, there have been differing results. Influences like age, culture, and personal stimulation are important factors in this phenomenon. Different chakra systems are well matched with different colors, and one of the chromotherapeutic methods is constructed to this chakra system as complementary and alternative medicine. However, as a consequence of the new findings and developments arising in color‐related research, we propose new model supported wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Chromotherapy is a treatment that exploits the chromatic properties of visible light to treat diseases such as aches, nosebleeds, and burns [ 1 ]. The color was often used for patient diagnostics for centuries; then, appropriate colored rooms—defined as ‘chromotherapy rooms’—were used for healing [ 2 ]. Chromotherapy rooms (CRs), also known as color therapy rooms, are places to enhance an individual’s mood, well-being, and health with the use of colored lights [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chromotherapy is a treatment that exploits the chromatic properties of visible light to treat diseases such as aches, nosebleeds, and burns [ 1 ]. The color was often used for patient diagnostics for centuries; then, appropriate colored rooms—defined as ‘chromotherapy rooms’—were used for healing [ 2 ]. Chromotherapy rooms (CRs), also known as color therapy rooms, are places to enhance an individual’s mood, well-being, and health with the use of colored lights [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emotional responses to colour has been studied in other contexts (O'Connor, 2011;Gul et al, 2015;Jonauskaite et al, 2020) and these provide a comparison for this study. Such studies suggest psychological responses varying with colour; red is used to excite, activate and arouse, blue to calm and relax, green to offer equilibrium, and yellow to uplift (Aktekin & S ¸imas ¸ek, 2012;Azeemi et al, 2019). However, colour therapies are typically conducted in artificial not natural environments (Aktekin and S ¸imas ¸ek, 2012;Vaquero-Blasco et al, 2020) Elsadek and Fujii (2014) suggested that entirely green plants promote a more comfortable environment compared to green-red and green-white variegated plants.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies suggest psychological responses varying with colour; red is used to excite, activate and arouse, blue to calm and relax, green to offer equilibrium, and yellow to uplift (Aktekin & S ¸imas ¸ek, 2012;Azeemi et al, 2019). However, colour therapies are typically conducted in artificial not natural environments (Aktekin and S ¸imas ¸ek, 2012;Vaquero-Blasco et al, 2020) Elsadek and Fujii (2014) suggested that entirely green plants promote a more comfortable environment compared to green-red and green-white variegated plants. Kexiu et al (2021) indicated a cultural context; green and green-white foliage plants enhanced relaxation and calmness in Japanese residents, while light green and green-yellow were the hues that were preferred for inducing calm in Egyptian participants.…”
Section: Introductionmentioning
confidence: 99%